Sodium thiosulfate-supplemented UW solution protects renal grafts against prolonged cold ischemia-reperfusion injury in a murine model of syngeneic kidney transplantation - George J. Dugbartey (Elsevier, 2022)
Introduction: Cold ischemia-reperfusion injury (IRI) is an inevitable event that increases post-transplant complications. We have previously demonstrated that supplementation of University of Wisconsin (UW) solution with non-FDA-approved hydrogen sulfide (H2S) donor molecules minimizes cold IRI and improves renal graft function after transplantation. The present study investigates whether an FDA-approved H2S donor molecule, sodium thiosulfate (STS), will have the same or superior effect in a clinically relevant rat model of syngeneic orthotopic kidney transplantation. Method: Thirty Lewis rats underwent bilateral nephrectomy followed by syngeneic orthotopic transplantation of the left kidney after 24-hour preservation in either UW or UW+STS solution at 4 °C. Rats were monitored to post-transplant day 14 and sacrificed to assess renal function (urine output, serum creatinine and blood urea nitrogen). Kidney sections were stained with H&E, TUNEL, CD68, and myeloperoxidase (MPO) to detect acute tubular necrosis (ATN), apoptosis, macrophage infiltration, and neutrophil infiltration. Result: UW+STS grafts showed significantly improved graft function immediately after transplantation, with improved recipient survival compared to UW grafts (p < 0.05). Histopathological examination revealed significantly reduced ATN, apoptosis, macrophage and neutrophil infiltration and downregulation of pro-inflammatory and pro-apoptotic genes in UW+STS grafts compared to UW grafts (p < 0.05). Conclusion: We show for the first time that preservation of renal grafts in STS-supplemented UW solution protects against prolonged cold IRI by suppressing apoptotic and inflammatory pathways, and thereby improving graft function and prolonging recipient survival. This could represent a novel clinically applicable therapeutic strategy to minimize the detrimental clinical outcome of prolonged cold IRI in kidney transplantation.